Macro-propagation and quality of plantain seedlings (Musa AAB Simmonds) as a function of substrates and sprout size - Cedeño-García, Galo Alexander; Vera-Macías, Leonardo Ramón; Velásquez-Cedeño, Sofía del Rocío; López-Álava, Geoconda Aracely; Cargua-Chávez, Jessica Elizabeth; Cedeño-García, George Alexander (Revista Colombiana de Investigaciones Agroindustriales, 2022)
The macro-propagation of plantain in a thermal chamber is an economical and efficient alternative method for quality seedling production. The aim of the research was to evaluate the effect of various substrate types and different sprout sizes on the production and quality of plantain seedlings propagated in a thermal chamber. Two separate experiments were performed. 1) To test the effect of four substrates on the plantain sprout production in a thermal camera, using cattle manure composted (CC), cattle manure composted + peanut husk (CC + PH), cattle manure composted + rice husk (CC + RH), and cattle manure composted + white sawdust (CC + WS). The sprout multiplication rate was recorded. 2) To test the effect of three sprout sizes on the growth and seedling quality in the nursery phase, using type A (6-10 cm), type B (11-15 cm), and type C (16-20 cm) sprouts. Variable growth and seedling quality were measured. A completely randomized design was used in both experiments. Analyses of variance and comparison of means (Tukey, p ≤ 0,05) were performed. The highest sprout multiplication rate was obtained with the CC + RH substrate. The highest growth and Dickson quality index on seedlings in the acclimatization phase were obtained with type C sprouts. The type of substrate and the size of the sprouts were decisive in the production and quality of macro-propagated plantain seedlings.